2005
DOI: 10.1093/gerona/60.4.432
|View full text |Cite
|
Sign up to set email alerts
|

Is the Val16Ala Manganese Superoxide Dismutase Polymorphism Associated With the Aging Process?

Abstract: Oxidative stress has been related to aging. Recent evidences suggest that a genetic dimorphism that encodes for either alanine or valine in superoxide dismutase (SOD2) is involved with oxidative stress. However, the current literature is still controversial, and the potential role of the Ala16Val polymorphism in human aging needs to be established. Here we investigated the role of the SOD2 polymorphism in: a) age-related mortality, b) morbidity (breast and prostate cancer), c) immunological markers, and d) DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 32 publications
2
33
0
1
Order By: Relevance
“…Subjects were recruited from the Cardiology Service, São Lucas Hospital (SLH), Brazil and from an epidemiological study of aging and non-transmissible diseases conducted in the metropolitan area of Gravatai, Porto Alegre. Previous genetic studies have been performed in this research project (24,25). Minimal and maximal ages were 35 and 92 years old, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects were recruited from the Cardiology Service, São Lucas Hospital (SLH), Brazil and from an epidemiological study of aging and non-transmissible diseases conducted in the metropolitan area of Gravatai, Porto Alegre. Previous genetic studies have been performed in this research project (24,25). Minimal and maximal ages were 35 and 92 years old, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, of the 22 studies (Wang et al, 2001;Woodson et al, 2001;Lin et al, 2003;Liu et al, 2004;Wang et al, 2004;Li et al, 2005;Taufer et al, 2005;Ho et al, 2006;Choi et al, 2007;di Martino et al, 2007;Ergen et al, 2007;Kang et al, 2007;Arsova-Sarafinovska et al, 2008;Iguchi et al, 2008;Mikhak et al, 2008;Bica et al, 2009;Cheng et al, 2009;Iguchi et al, 2009;Sun et al, 2009;Zejnilovic etal., 2009), the sample size ranged between 100 and 3,030, and there were twelve studies on prostate cancer, four studies on esophageal cancer, and six studies on lung cancer. All studies, except for five of them (Taufer et al, 2005;Bica et al, 2009;Sun et al, 2009;Zejnilovic et al, 2009), indicated that the distribution of genotypes in the controls was consistent with HardyWeinberg equilibrium, while only one study conducted by Lin et al (2003) contained no data for Hardy-Weinberg equilibrium.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In prostate cancer, we excluded three studies (Taufer et al, 2005;Ergen et al, 2007;Bica et al; because their controls were not in Hardy-Weinberg equilibrium and we found that the data did not statistically alter the conclusions of our analysis in the homozygote model (Ala/ Ala versus Val/Val, OR = 1.13; 95% CI = 1.01-1.27) or dominant model (Val/Ala+Ala/Ala versus Val/Val, OR = 1.11; 95% CI = 1.01-1.22). In the subgroup analysis by disease stages, one study (Wang et al, 2001) was excluded because the control was not in Hardy-Weinberg equilibrium.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Previous studies have investigated a mutation at c.47T > C (rs4880 polymorphism) in the SOD2 gene and its potential correlation with POAG; results though remain controversial [18][19][20]. Because of: the important role of mitochondria in retinal ganglion cells apoptosis, the increasing evidence of oxidative stress involvement in many pathologic conditions [21,22] including glaucoma, the presence of Mn-SOD enzyme in mitochondria and controversial results from previous studies, we decided to investigate whether this mutation is a risk factor for POAG in Greek population. …”
Section: Introductionmentioning
confidence: 99%